PREVALENCE OF HEPATITIS C VIRUS (HCV) AMONG THALASSEMIAPATIENTS IN IBN-ALBALADY HOSPITAL - Abed, Baydaa Ahmed (Al-Nahrain Journal of Science, 2010)
thalassemia is one of most dangerous disease; it is an inherited impairment of hemoglobin production, in which there is partial or complete failure of the synthesis of globin chain.Objective: the aim of this study is to determine the prevalence of Hepatitis C Virus (HCV) infection among thalassemic patients in Ibn-albalady hospital in Baghdad. Patients and methods: The study was carried out on 111 transfusion dependent beta-thalassemia (74 males and 37 females) with a mean age 12.51 yrs attending to the Ibn Alba lady Hospital, in Baghdad during the period March 2008 to September 2008. The control group was thirty one (12 males and 19 females) with mean age of 11.5 yrs and investigated to serve as a control group; they were randomly selected from community. Blood sample was collected in morning for biochemical assays (hepatitis C virus (HCV), Glutamic Oxaloacetic (GOT),Glutamic Pyruvic Transaminase (GPT), Alkaline phosphates (ALP), Total serum bilirubin (TSB), Direct serum bilirubin( Dir.SB), Indirect serum bilirubin (Indir.SB).Results: Out of 111 thalassemic patients there was 51 (46 %) sera was confirmed positive for antiHCV- antibodies. The remaining 60 (54 %) were seronegative, while among 31 healthy controls only one (3.22%) was seropositive the result was statistically of a high significant difference (P=0.0001).Out of 51 seropositive, 13 (72.3%) patients were positive among those above 20 years, while only one (16.7) was positive among those from (0 4) years. It was found no significant correlation in (sex, TSB, Indir.SB, ALP) between patients with HCV+ve compared with HCV -ve. The current study demonstrated that there was a highly significant difference in (GPT, GOT, and Dir.SB) levels between patients with seropositive HCV and patients with seropositive HCV. Conclusions: The main causes of liver injury in thalassemia are hepatitis C virus and the finding suggests that HCV is the main cause of abnormal liver function in patients with thalassemia.